2016
DOI: 10.1111/ijd.13308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MicroRNA‐21 induces apoptosis in dermal fibroblasts of patients with systemic sclerosis

Abstract: Although further studies are necessary to determine the underlying apoptotic pathway, we propose that inhibition of miR-21 in dermal fibroblasts from lesional skin may be useful in harnessing progressive fibrosis in SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Recent studies have focused on the role of epigenetics such as miRNAs in skin-involved autoimmune diseases specially SSc. 41,42 Furthermore, dysregulated survivin-targeting miRNAs have provided new perspectives in the field of cancer. 23 Therefore, much more needs to be learned about the regulatory role of survivin-targeting miRNAs in SSc.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the role of epigenetics such as miRNAs in skin-involved autoimmune diseases specially SSc. 41,42 Furthermore, dysregulated survivin-targeting miRNAs have provided new perspectives in the field of cancer. 23 Therefore, much more needs to be learned about the regulatory role of survivin-targeting miRNAs in SSc.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the powerful gene regulators microRNAs have been implicated in many pathophysiological processes, including cell development, proliferation, apoptosis, and carcinogenesis [20,38,39]. Accumulating evidence has shown that many miRNAs are also critically involved in the pathogenesis of human tissue fibrosis of in several organs [40].…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 Inhibition of miR-21 expression induced apoptosis in SSc fibroblasts [24] Melanoma SPRY1, PDCD4 and PTEN Affects the proliferation, migration, and apoptosis of human melanoma A375 cells [25] miR-29…”
Section: Ptenmentioning
confidence: 99%